The State of the Info-communication Markets in Dél-Alföld Region – Hungary - Kanalas, Imre; Nagy, Gábor (Discussion Papers, 2012)
The strategic development direction helping and supporting the development of information society appeared relatively soon. The conceptions of the counties handle the development of telecommunication networks, the problem of the socialization of information technologies and the establishment of the informational basis supporting certain ICT-spheres of action as an advanced developmental programme. We should pay attention to the fact that the importance of the obtainment of information, the spreading of the forms of informatics instruction appear among the content elements of the programmes. The Information Society’s elements are important part of the wider economic development, in relation to the advanced, continuous and quick tune development of the informatics and telecommunication infrastructure, the introduction of IT-industries indicating the desirable direction of the restructuring of economy and the settling and the access of high-level business services helping the healthy operation of economy and the shaping public administration to ‘more company-friendly’. Foreshadowing initiations started in relation to the introduction of electronic administration, the establishment of e-government system in the governments of the region. The regional and local marketing, the image building, the identity-shaping, the local and regional value conveying might be outstandingly efficient with the help of informational devices comparing with the channels used for conventional information transmission. Also the ICTs became an effective mediatory channel of the conservation and the conveyance of culture. The role formed for the information technologies in the complex handling of the problems of the ‘tanya’ (farmstead) area can be regarded as a model, where the local initiative developmental strategy served as a model for the establishment of the national-level politics. If this attitude and activity is maintainable, the present backwardness of Dél-Alföld in the key-fields of Information Society turned it into advantage.